Short Communication: Incidence of insect pest on planted Shorea macrophylla at reforestation sites in Gunung Apeng National Park, Sarawak, Malaysia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sidi MB, Wasli ME, Polly E, Jaffar ANNM, Kalu M, Sani H, Nahrawi H, Elias H, Omar D. 2021. Short Communication: Incidence of insect pest on planted Shorea macrophylla at reforestation sites in Gunung Apeng National Park, Sarawak, Malaysia. Biodiversitas 22: 5162-5168. Incidence of insect pest in Shorea macrophylla (de Vriese) P.S. Ashton had critical foliage damage in mono planting technique. The main objectives were to assess the foliage damage intensity of planted S. macrophylla by age stands and type of foliage damage. The insect pest attacks the foliage of S. macrophylla was determined. The study site was located at Gunung Apeng National Park (GANP), Sarawak, Malaysia, with planted S. macrophylla in enrichment planting at different years (planted in 2008, 2009, 2010, and 2011 for age stand 6, 5, 4, and 3, respectively). The results showed that the degree of foliage damage decreases with the age stand of S. macrophylla tree. Therefore, foliage damage was suspected to be caused by insect pests. Among the common foliage damages observed was "hole damage" caused by insect order Lepidoptera. Although foliage damage was significant, the severity of the damage will "heal" as the age stand increases. Further investigation on other possible causes of these pest attacks should be initiated to find solutions that may hasten the growth of planted S. macrophylla for forest restoration.
Keywords: age stands; foliage damage; insect pest; Shorea macrophylla